Trees for development? Articulating the ambiguities of power, authority and legitimacy in governing Ghana's mineral rich forests. Issue 3 (August 2015) - Hirons, Mark
Abstract: The growth of mining activities in Africa in the last decade has coincided with increased attention on the fate of the continent's forests, specifically in the contexts of livelihoods and climate change. Although mining has serious environmental impacts, scant attention has been paid to the processes which shape decision-making in contexts where minerals and forests overlap. Focussing on the illustrative case of Ghana, this paper articulates the dynamics of power, authority and legitimacy of private companies, traditional authorities and key state institutions in governing mining activities in forests. The analysis highlights how mining companies and donors promote a neoliberal model of resource management which entrenches their ability to benefit from mineral exploitation and marginalises the role of state institutions and traditional authorities in decision-making. This subsequently erodes state authority and legitimacy and compounds the contested nature of traditional authorities' legitimacy. A more nuanced examination of foundational governance questions concerning the relative role of the state, traditional authorities and private interests is needed.